Treasury Reuse and the Demand for Safe Assets - Infante, Sebastian; Saravay, Zack (Review of Financial Studies, 2025)
We theoretically and empirically show how the reuse of Treasury securities as collateral alleviates safe asset scarcity. Our model characterizes how reuse allows intermediaries to efficiently reallocate the safety benefits of long-term Treasury securities to a broader investor base. By reusing Treasury securities, intermediaries can access more collateral to create safe assets without interest rate risk. When the demand for safe assets is high, intermediaries increase reuse, distributing safe asset benefits to investors that value safety the most. Using supervisory data to calculate a dealer-level measure of reuse called the “collateral multiplier,” we empirically confirm the model’s main predictions.